The bird population of Tétényi-plateau in 2003–2004 - Bajor, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2004)
The bird population of Tétényi-plateau researched by the author in the year 2003-2004. The total number of species recorded were 95 in the period of research (33 breeder, 21 potentionally breeder, 10 common migrant, 10 common wintering vagrant and 21 rare vagrant). The plateau seems to be rich in birds, so it is worth continuing and extending the research in the future.
Keywords: protecetd area; bird population